Financial distress di sektor property and estate: Tinjauan empiris atas kinerja keuangan perusahaan terbuka di Indonesia - Nicky Clara Khelle K; Risanda Alirastra Budiantoro (Nur Science Institute, 2025)
Financial distress is an important issue that affects business continuity and economic stability. This study examines the effect of liquidity, leverage, profitability, and company size on financial distress in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Using a quantitative approach with panel data, 22 companies were selected through purposive sampling technique. The analysis was carried out using panel data regression with the best model, namely the Common Effect Model (CEM), through the Eviews 12 application. Financial distress is measured using the Altman Z-Score proxy. The results showed that leverage has a positive and significant effect on financial distress, then profitability and company size have a significant negative effect on financial distress. Meanwhile, liquidity has no significant effect. However, the four variables simultaneously have a significant effect. These findings indicate that it is necessary to strengthen the company's internal policies in managing its financial structure wisely, in order to mitigate the risk of financial distress.